Insights into gender-equity in healthcare accessibility in northern Nigeria: descriptive and predictive approaches - Chika Yinka-Banjo; Olasupo Ajayi; Mary Akinyemi; David Tresner-Kirsch; Adekemi Omotubora (Healthcare in Low-resource Settings, 2025)
Insights into gender-equity in healthcare accessibility in northern Nigeria: descriptive and predictive approaches.